(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث تحضير عينات من الألمينوسيليكات ذات البنية الميزومسامية عند نسب مختلفة من SiO2/Al2O3= 20,40,80 , وذلك في درجة حرارة الغرفة, وكذلك بالمعالجة الهيدروحرارية عند الدرجة 100ºC لمدة 24 ساعة باستخدام سيتيل ثلاثي ميتيل أمونيوم بروميد كعامل موجه للبنية . لوحظ تشكل بنية منتظمة ميزومسامية من النوع MCM-41 بوجود العامل الموجه للبنية, و عدم تشكل البنية في العينات المحضرة بغياب العامل موجه للبنية . استخدمنا طرائق مختلفة لتوصيف العينات الناتجة, وهي طريقة امتزاز النيتروجين عند الدرجة 77K لتحديد البنية النسيجية للعينات من خلال تحليل بيانات الامتزاز, وطريقة التحليل الحراري ألوزني التفاضلي TG-DTA لمعرفة الآثار الحرارية المرافقة و ثبات البنية , طريقة FTIR لمعرفة الارتباطات الموجودة داخل البنية المتشكلة و طريقة XRD لتحديد الطور المتشكل . تمت دراسة إمكانية امتزاز أزرق الميتيلين من محاليله المائية, وذلك لتحديد الفة هذه البنى لامتزاز الألوان من المحاليل . In this work, some samples of Aluminosilicate with mesoporous structure were prepared at different molar ratio SiO2/Al2O3= 20, 40, 80, at room temperature and hydrothermal treatment (100ºC) for 24 hours. This treatment was done using acetyl trimethyl-amonium bromide as a structural directing agent. It has been remarked a formation of a ordered mesoporous structure (MCM-41). There is no structural formation without a directing agent. The methods used to characterization the resulting structure were : Nitrogen adsorption at 77K to determine the textural structure ,TG- DTA to determine the thermal effects and stability of the structure, FTIR to determine the types of surface bonds and XRD to verify the type of crystalline phase, was studied to determine the affinity of resulting structures to adsorption of colors from solutions .